E-Comic as an Alternative Learning Media for Analytical Mechanic Course During COVID-19 Pandemic - Bella, Alya Nurfita; Nuryaman, Afini Vinnahari; Cahyani, Marini Ayu; Setiaji, Bayu (Impulse: Journal of Research and Innovation in Physics Education, 2021)
The covid-19 pandemic era causes teaching and learning activities to be carried out online. Thus, many variations of learning media are used to conduct teaching and learning activities in the pandemic era. This research developed one learning media that uses e-comics or electronic comics. The comic is expected to be a learning medium worth using in the pandemic era. This research aims to develop the medium of learning physics comics on the history of analytical mechanics. The research method used is the research and development method, covering data stages, product design, product testing. The software used in creating comics was ibisPaint X and MediBang Paint. The findings of this study are that E-comic improves reading culture. E-comics as an alternative learning media in analytical mechanics courses during the covid-19 pandemic is very worthy of being used as learning media.